Ang tala - Dormiendo, Arlei Eniceo 1992-; Tolentino, Rolando B.; University of the Philippines. College of Mass Communication (2013)
"Death is an inevitable experience that all humans must eventually face. The acceptable time for a person to die is during his old age because then, he has had enough time to have lived his life fully. A child's death is most devastating because due to her short time in the planet, people are led to believe that the child has not yet lived her life to the fullest. Ang Tala is an animated short film chronicling ordinary events in the life of a little girl until it is tragically cut short by a debilitating disease. These events juxtaposed with title cards with typical bucket list entries and/or life milestones show the little girl achieveing said entries and milestones but in her own way."
Vita.
Thesis (A.B. Film and Audiovisual Communication)--University of the Philippines Diliman
Keywords: Children and death